Inactivation of Vibrio anguillarum by Attached and Planktonic Roseobacter Cells - D'Alvise, Paul W. (American Society for Microbiology (ASM), 2010)
The purpose of the present study was to investigate the inhibition of Vibrio by Roseobacter in a combined liquid-surface system. Exposure of Vibrio anguillarum to surface-attached roseobacters (10(7) CFU/cm(2)) resulted in significant reduction or complete killing of the pathogen inoculated at 10(2) to 10(4) CFU/ml. The effect was likely associated with the production of tropodithietic acid (TDA), as a TDA-negative mutant did not affect survival or growth of V. anguillarum.